Comparative bioavailability study of two salbutamol tablets in healthy adult volunteers - Chik, Z.; Basu, R.C.; Pendek, R.; Lee, T.C.; Mohamed, Z. (2009)
This study was carried out to compare the rate and extent of absorption of a generic salbutamol in oral dosage form (Brethmol, 4mg) with the proprietary equivalent product (VentolinÂ®, 4mg), in healthy adult subjects, under fasting conditions. The study was a single dose, randomized, two way crossover study with a four-week washout period. It involved 22 healthy volunteers who received a single dose (4mg) of the test and the reference products after an overnight fast of at least 10 hours. Blood samples were collected at pre-dose and a serial of 14 samples were collected from each of the subject from 1h until 48 h post-dose. Plasma concentrations of salbutamol were analyzed using GCMS method. The mean AUC 0-â values were 91.26 and 96.45 h.ng/ml for reference and test product, respectively. The mean C max values were 12.26 and 12.38 ng/ml and the mean t max values were 2.80 and 2.33 hours for reference and test product, respectively. Analysis of variance showed that the 90 confidence intervals on the relative difference of the ratio for the AUC 0-â and the C max for the test and reference products were contained within the bioequivalence limit (80 - 125) (C max: 89.8 - 110.5 and AUC 0-â: 91.6 - 121.5). There was no statistically significant difference for the t max between the test and reference formulations (p = 0.30). The test formulation was found to be bioequivalent to the reference formulation with regard to AUC 0-â and C max. There was no statistically significant difference in Brethmol and VentolinÂ® t max. In conclusion, Brethmol and VentolinÂ® are bioequivalent in healthy subjects. Â© 2009 Dustri-Verlag Dr. K. Feistle.